Postcolonial Travel Writing
IX, 192 p.
Keywords: With its inclusion of original essays challenging the view of travel writing as a Eurocentric genre, this book will stand as a benchmark study of future inquiries in the field. It will revitalize the critical debate, sparking a much needed rethinking of a vibrant and highly popular but also volatile genre that has seen many changes in recent years.